STUDI KASUS PEMELIHARAAN DAN KELAYAKAN ALAT PELINDUNG RADIASI LEAD APRON - Wati, Retno; Agus, Mohammad Bimo Alfarel; Zen, Taufiq Fachruddin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Lead apron is one of the most important things as an individual radiation protection device in a Radiology Installation. At the Central Radiology Installation of the Orthopedic Hospital of Prof. Dr. R. Soeharso Surakarta, the last leak test was carried out in 2018 which was then carried out a feasibility test on the lead apron which was suspected of being damaged but still in use. This study aimed to determine the procedure for testing the suitability of lead apron, the results of testing the feasibility of lead apron, and the maintenance of lead apron. This research method applied a case study approach. This research was conducted at the Central Radiology Installation of Orthopedic Hospital of Prof. Dr. R. Soeharso Surakarta from April 2022 to July 2022. The subjects of this study were 2 radiation protection officers and 1 medical physicist. Data collection was carried out by means of observation, interviews and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The result of the research was that the maintenance of lead apron at the Central Radiology Installation of Orthopedic Hospital of Prof. Dr. R. Soeharso Surakarta can be in the form of storage and cleaning. In storage it was placed horizontally in a special lead apron rack, and several lead aprons are stacked, and cleaning was done by cleaning Pb with alcohol and wet tissue when visibly dirty. The results of the lead apron leak test showed that the lead apron 1,2,3,5,6,7 had unfit conditions. The author's suggestion is that lead aprons that are damaged and do not meet eligibility standards are immediately rejected or not used for the safety of staff or patient families and replaced with new lead aprons. To maintain the function and durability of the lead apron, more attention should be performed to maintenance methods.